Noninvasive Capnometry for End-tidal Carbon Dioxide Monitoring via Nasal Cannula in Nonintubated Neonates - Chih-Che Tai; Frank Leigh Lu; Pau-Chung Chen; Suh-Fang Jeng; Hung-Chieh Chou; Chien-Yi Chen; Po-Nien Tsao; Wu-Shiun Hsieh (Pediatrics and Neonatology)
Arterial blood gas analysis is the gold standard for assessing the adequacy of ventilation. However, arterial blood sampling may be associated with serious complications in neonates. The aim of the study was to utilize the side-stream capnometry measurement of end-tidal carbon dioxide (PetCO2) via nasal cannula circuits and to verify the reliability of PetCO2 in reflecting the arterial blood carbon dioxide (PaCO2) level in nonintubated neonates. Methods: A retrospective medical record review analysis was performed in nonintubated neonates admitted to the neonatal ward in a medical center. Simultaneous arterial PaCO2 and PetCO2 levels were evaluated. PaCO2 and PetCO2 levels were compared by paired t test and were correlated using Pearson's correlation. The PetCO2 bias was defined as the difference between PaCO2 and PetCO2, and was assessed by Bland-Altman plot analysis. Results: A total of 34 neonates were recruited, and data of 54 pairs of PaCO2 and PetCO2 levels were available for comparison. The average (mean ± SD) gestational age was 32.5 ± 4.2 weeks, and the average birth weight was 1881 ± 1077 g. There was a good correlation between PetCO2 and PaCO2 levels among all paired samples (r = 0.809, p < 0.001). When the data were divided into those with respiratory disease (n = 34) and those without (n = 20), significant correlation between PetCO2 and PaCO2 levels were both noted in the former group (r = 0.823, p < 0.001) and the latter group (r = 0.770, p < 0.001). The overall average mean value of PetCO2 was lower than that of PaCO2 (39.4 ± 8.8 mmHg vs. 41.3 ± 9.2 mmHg, p = 0.014). The difference between PetCO2 and PaCO2 levels was significant only among those with respiratory disease (38.8 ± 9.8 mmHg vs. 41.2 ± 10.3 mmHg, p = 0.027), but not among those without (40.5 ± 7.0 mmHg vs. 41.6 ± 7.2 mmHg, p = 0.289). Conclusions: End-tidal CO2 measurement by side-stream capnometry through nasal cannula could provide an accurate and noninvasive estimate of PaCO2 levels in nonintubated neonates.